2016
DOI: 10.3390/rs8080664
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Landscape Trends on Agriculture, Introduced Exotic Grasslands and Riparian Ecosystems in Arid Regions of Mexico

Abstract: Riparian Zones are considered biodiversity and ecosystem services hotspots. In arid environments, these ecosystems represent key habitats, since water availability makes them unique in terms of fauna, flora and ecological processes. Simple yet powerful remote sensing techniques were used to assess how spatial and temporal land cover dynamics, and water depth reflect distribution of key land cover types in riparian areas. Our study area includes the San Miguel and Zanjon rivers in Northwest Mexico. We used a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 54 publications
4
36
1
1
Order By: Relevance
“…Previous land use and vegetation classification studies in the area have found that agriculture and cattle ranching are the activities that contribute the most to land cover dynamics [8], which is consistent with the present study given that those activities were present in all of the study sites and are determinant to the disturbance degree of riparian habitats. Different indices that evaluate ecological parameters in riparian habitats have been used in many places in Mexico [15,[58][59][60], all of them use vegetation parameters such as composition, cover and species density to estimate riparian habitat condition.…”
Section: Disturbance In the Smr Watershedsupporting
confidence: 81%
See 3 more Smart Citations
“…Previous land use and vegetation classification studies in the area have found that agriculture and cattle ranching are the activities that contribute the most to land cover dynamics [8], which is consistent with the present study given that those activities were present in all of the study sites and are determinant to the disturbance degree of riparian habitats. Different indices that evaluate ecological parameters in riparian habitats have been used in many places in Mexico [15,[58][59][60], all of them use vegetation parameters such as composition, cover and species density to estimate riparian habitat condition.…”
Section: Disturbance In the Smr Watershedsupporting
confidence: 81%
“…Our class scheme (Table 4) was developed using observations from the field (regarding community composition and stand physiognomy) and previous classification studies conducted in the area [8]. In order to simplify the classification scheme, all desert vegetation types adjacent to the river is referred to as "Desert Scrub", even though the formal designation for the Plains of Sonora region (as described by Shreve and Wiggins 1964 classification) is Arbosuffrutescent Desert.…”
Section: Land Cover Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…CART models have proven useful for creating general vegetation classifications from spectral data [46] and have been successfully used to model changes in arid land riparian vegetation [47,48]. Additionally, they are rule-based and use independent variables and datasets to determine the correct class membership for each pixel [46].…”
Section: Land Cover Classification Systemmentioning
confidence: 99%